California Advocate's Drum Major for Justice Dinner Honoring Julian Bond - Watkins, Howard::::::::: (1987)
William Riddlesprigger seated to left of lectern, Les Kimber standing, Julian Bond speaking, Pauline Kimber and Mark Kimber standing